Nicaragua : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that during the past two years, macroeconomic developments in Nicaragua have been generally favorable. Real GDP grew by an average of 5u percent during 2011-2012, and the annual average inflation was 7u percent during the same period. Looking ahead, the macroeconomic outlook also remains broadly positive. Real GDP is expected to grow by 4u percent in 2013 and then stabilize at its potential level of 4 percent over the medium-term. Inflation is projected to remain at about 7 percent supported by the crawling-peg exchange rate system that has helped anchor inflation expectations.